Gamma Radiation Synthesis and Characterization of Silver and Gold Nanoparticles in Polymer Matrices - Naghavi, Kazem (2011)
Nanoparticles are referred to nanostructure materials having dimensions in the range of 1 − 100 nm and typically contain few hundred to few thousand atoms. They may compose of single or more elements to form zero-dimensional nanomaterials such as metal nanoparticles, semiconductor quantum dots, colloids, and clusters. Nanoparticles exhibit unusual optical, electronic, magnetic and chemical properties dissimilar to the properties of their molecular and bulk materials due to their quantized nature and large surface area-to-volume ratios. Noble metal nanoparticles such as silver (Ag) and gold (Au) nanoparticles embedded in polymer matrices present high catalytic activity, remarkable optical effects such as light absorption, surface enhanced Raman scattering (SERS), and extraordinary optoelectronic and electronic properties useful for biosensors and electronic devices. The shape, size,and nanoparticle distribution density of metal nanoparticles and the ambient conditions are crucial parameters to understand the physics and chemistry phenomena of matter at nanometer scales. The potential technological applications depend on our capability to control these parameters during synthesis. Of various reduction methods including chemical, photochemical, electrochemical, and sonochemical techniques, the radiation-induced production method offers clean, harmless, controllable size, highly pure and stable nanoparticles, and free from reducing agents or impurities. In this works, colloidal Ag and Au nanoparticles were synthesized using gamma-radiation method by reducing silver ions of silver nitrate (AgNO3 concentration between 3.7 ×10-4 and 21.0 × 10-4 M) and gold ions of tetrachloroauratehydrate (HAuCl4 concentration between 1.0 × 10-4 and 7.5 × 10-4 M) stabilized by 4.7% poly(vinyl alcohol) (PVA) and 5.6% poly(vinyl pyrolidone) (PVP). All the samples at different concentrations of silver and gold salts were irradiated with doses of 10, 20, 30, 40, 50, 60, 70 kGy using a 60Co γ-rays radiation source. Upon gamma irradiation, free electrons, hydrated electrons, and free radicals that are produced able to produce the Ag+ and Au3+ ions into Ag0 and Au0 atoms prior to an aggregation to form (Ag0)n and (Au0)n nanoparticles respectively. The formation of Ag and Au nanoparticles have been observed by the change in color of the colloidal samples from colorless to golden yellow for Ag nanoparticles and to red for Au nanoparticles. The presence of Ag and Au metals were confirmed by the Energy Dispersive X-ray Spectroscopy (EDX) elemental analysis. The size of Ag and Au nanoparticles were determined at 90% cumulative distribution of the Photon Cross Correlation Spectroscopy (PCCS) and confirmed by the Transmission Electron Microscopy (TEM). The average diameter of colloidal Ag and Au nanoparticles decreases with increasing dose and increases with increasing starting salts concentration. The minimum diameters achieved were at 12 and 2 nm respectively for Ag and Au nanoparticles in PVP obtained from the lowest salts concentration and the highest radiation dose at 70 kGy. This radiation-induced nucleation event has been described as a dose-dependent process and the kinetics of nucleation of Ag and Au nanoparticles stabilized in PVA and PVP have been quantitatively studied. At high doses, where the nucleation event is more than the total metal ions, the radiation synthesis produced smaller sizes of nanoparticles following aggregation. On the other hand, at low doses were the nucleation event is less than the total metal ions, the radiation synthesis produced larger sizes of nanoparticles. The shape of Ag and Au nanoparticles were spherical in shape as determined by TEM method. The optical properties of Ag and Au nanoparticles were measured by means of UV-Visible absorption spectrophotometer. The presence of Ag and Au nanoparticles was revealed at the absorption peaks between 400 and 425 nm for Ag nanoparticles and between 500 and 550 nm for Au nanoparticles depending on the salts concentration and radiation dose. The maximum absorbance of the colloidal Ag and Au nanoparticles increases with increasing radiation dose, indicating an increase of the nanoparticle distribution density of Ag and Au nanoparticles at higher doses. Exceptional for radiation-induced synthesis, the absorption peaks shifted to lower wavelengths or blue-shift with increasing radiation dose indicating the diameter of Ag and Au nanoparticles decreases with increasing dose. Consequently, this gave a confinement effect on the conduction band of Ag and Au nanoparticles, which increases with the decrease of nanoparticle diameter. The fundamental characteristics of Ag and Au nanoparticles have been explained in terms of the quantum mechanical description for metal nanoparticles deviating from the more established concept of the surface Plasmon resonance derived from the classical electrodynamics theory.